The effect of special exercises on perceptual speed and learning some ground movements in gymnastics (Journal of the College of Basic Education, 2022)
The research included four chapters, as the first chapter included the introduction and the importance of research, as the importance of research lies in the importance of research in the preparation of exercises, especially in cognitive speed and learning some of the earth movements in your skull, but the problem of research lies in the problem of research in the weakness in the level of performance of children, which is due to the lack of diversification in the use of new educational methods to simplify understanding and understanding the correct performance of the skills of your artistic skull in describing the movement. The goal of the research is to prepare special exercises in cognitive speed and learn some ground movements of the skull. For the benefit of remote tests, there are statistically significant differences between the results of the remote tests of the experimental and controlled research groups and in favour of the experimental group in some ground movements in the gymnasts. The second chapter included the research curriculum and its field procedures used the experimental method, but the sample of the research was represented by the cubs of the Baghdad Secretariat Sports Club, which numbered 8 children divided into two experimental and controlled groups of (4) per group. The fourth chapter also included presenting and analysing the results of tribal and remote tests of the experimental and controlling groups and discussing them.Chapter 5 included the findings and recommendations of the researcher that both groups (experimental and controlled) have a positive impact on learning the skills of your skull and cognitive-motor abilities (in question). The proposed educational program and its dynamic cognitive exercises are more influential than the program used to develop the level of children. The need to follow the foundations and scientific methods when developing special exercises and presenting them to experts.